Pengaruh Promosi, Online Customer Review, dan Online Customer Rating terhadap Keputusan Pembelian Produk Makanan pada Layanan Shopee Food di D.I Yogyakarta - Agustiningsih, Luluk; Hartati, Retno (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the effect of promotions, online customer reviews, and online customer ratings on purchasing decisions for food products at Shopee Food services in D.I. Yogyakarta. This type of research is a quantitative research that is descriptive in nature. The population in this study are all people who live in D.I. Yogyakarta, which has purchased food products on the Shopee Food service. The sampling technique was carried out using non-probability sampling with a purposive sampling method. The number of samples is 150 respondents. The data collection method uses a questionnaire distributed through the Google form. Data analysis in this study includes validity test, reliability test, classical assumption test, F test (goodness of fit test), multiple linear regression analysis, t test and coefficient of determination test (RÂ²). The results of this study indicate that 1) promotions have a positive and significant effect on purchasing decisions, 2) online customer reviews have a positive and significant effect on purchasing decisions, and 3) online customer ratings have a positive and significant effect on purchasing decisions.